2015
DOI: 10.1097/shk.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surfactant Proteins A and D in Sepsis-Induced Acute Kidney Injury

Abstract: Sepsis is a major cause of acute kidney injury (AKI) with high rates of morbidity and mortality. Surfactant proteins A and D (SP-A, SP-D) play a critical role in host defense and regulate inflammation during infection. Recent studies indicate SP-A and SP-D are expressed in the kidney. The current study examines the role of SP-A and SP-D in the pathogenesis of sepsis-induced AKI. Wild-type (WT) and SP-A/SP-D double knockout (KO) C57BL/6 mice were treated by cecal ligation and puncture (CLP) or sham surgery. His… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…Our previous study also found SP-A/D KO mice had higher basal level of autophagy in liver and a more pronounced inflammatory response to sepsis than WT mice 46,47 . Of interest, in the present study, we observed uninfected SP-A/D KO mice exhibit significant higher basal levels of p38 MAPK phosphorylation compared with uninfected WT mice.…”
Section: Discussionmentioning
confidence: 66%
“…Our previous study also found SP-A/D KO mice had higher basal level of autophagy in liver and a more pronounced inflammatory response to sepsis than WT mice 46,47 . Of interest, in the present study, we observed uninfected SP-A/D KO mice exhibit significant higher basal levels of p38 MAPK phosphorylation compared with uninfected WT mice.…”
Section: Discussionmentioning
confidence: 66%
“…11 In addition, SP-A and SP-D attenuate kidney injury by modulating inflammation and apoptosis in sepsis-induced acute kidney injury 12 . However, whether or not SP-A plays a role in the process of non-infectious renal diseases, especially the chronic kidney diseases, the major cause of renal failure, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptotic cells were detected by means of a deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) kit (Roche, Indianapolis, IN) according to the manufacturer’s instructions. Cell apoptosis was quantified by counting the number of TUNEL-positive cells in 20 random fields at ×400 magnification (20). …”
Section: Methodsmentioning
confidence: 99%
“…Frozen lungs were homogenized in RIPA buffer containing a cocktail of protease- and phosphatase-inhibitors (Roche), and the supernatants were used for Western blot analysis (20). Total protein concentrations of samples (lungs and BALF) were determined using the BCA micro assay kit (Thermo Scientific, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation